NAVIGATING THE ENERGY TRANSITION: GREEN ECONOMY STRATEGIES IN THE FACE OF GLOBAL CLIMATE CHANGE CHALLENGES - Loso Judijanto; Al-Amin (INTERNATIONAL JOURNAL OF FINANCIAL ECONOMICS, 2025)
Global climate change has become a serious challenge that drives the need to transition to a green economy as a solution to realising sustainable development. This article discusses strategies for navigating the energy transition through the adoption of a green economy, which includes the development of green technologies, investment in renewable energy infrastructure and policies that promote sustainable business practices. It also highlights key challenges, such as resistance from fossil fuel-based industries, the need for financial support and technology gaps between countries. With international collaboration and multi-stakeholder commitment, an effective and equitable energy transition can be realised. In conclusion, the green economy provides a profound and strategic approach to climate change mitigation while emphasising the importance of transforming the global energy system for long-term sustainability.